Admission hypothermia in preterm infants seen at a public tertiary hospital, south-western Nigeria - Bolaji, Olufunke Bosede; Ajigbotosho, Samuel Olu; Ajetunmobi, Wasiu Adegbenga; Ajibola, Inimfon; Adesuji, Ademola; Onumajuru, Bartholomew (International Journal of Research in Medical Sciences, 2023)
Background: Hypothermia is associated with increased morbidity and mortality in neonates particularly in preterm infants who may need referral to tertiary centres to access care. The study aimed to document the incidence and characteristics of admission hypothermia in preterm infants seen in the neonatal unit of our hospital. Methods: A retrospective study reviewing the 1-year clinical records of admissions into our neonatal unit. Core temperature is routinely taken for all babies at admission with a low-reading digital thermometer. Hypothermia was defined as temperature <36.5℃; and subclassified into mild (36.0-36.4℃), moderate (32.0-36.0℃) and severe (<32℃). Statistical analysis was with Chi square analysis, student’s t-test, and Spearman correlation. P was set at 0.05. Results: During the study period, 278 babies were admitted into our neonatal unit of which 87 (31.3%) were preterm and 191 (68.7%) were term. The incidence of admission hypothermia in preterm infants was 35.6% and 15.2% in term babies (p=0.0003). There was a higher incidence of hypothermia in outborn (62%) compared to inborn babies (52%) (p=0.71). A strong positive correlation existed between the degree of hypothermia and both the gestational age and birthweights of the preterm infants; for mild hypothermia, p=0.002 while for moderate hypothermia, p=0.000. There was a higher mortality in preterms with hypothermia compared to those without hypothermia (p=0.22). Conclusions: A high incidence of admission hypothermia in preterm infants is reported in this study. Commencing immediate kangaroo mother care for preterm infants irrespective of the place of birth could help address this problem.